2018
DOI: 10.3390/ijms19071874
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Crystal Structures, and Antitumor Activities of Copper(II) and Nickel(II) Complexes with 2-((2-(Pyridin-2-yl)hydrazono)methyl)quinolin-8-ol

Abstract: Two transition metal complexes with 2-((2-(pyridin-2-yl)hydrazono)methyl)quinolin-8-ol (L), [Cu(L)Cl2]2 (1) and [Ni(L)Cl2]·CH2Cl2 (2), were synthesized and fully characterized. Complex 1 exhibited high in vitro antitumor activity against SK-OV-3, MGC80-3 and HeLa cells with IC50 values of 3.69 ± 0.16, 2.60 ± 0.17, and 3.62 ± 0.12 μM, respectively. In addition, complex 1 caused cell arrest in the S phase, which led to the down-regulation of Cdc25 A, Cyclin B, Cyclin A, and CDK2, and the up-regulation of p27, p2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…So far, hydrazone-based metal complexes have received considerable attention from chemists in many applications such as chromogenic reagents in the spectrophotometric determination of transition-metal ions, metal extracts and biologically active compounds [ 9 ]. They have also been demonstrated to possess diverse pharmacological properties [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], catalytic properties [ 18 , 19 ], adsorption properties [ 20 , 21 ], electrochemical properties [ 22 ], luminescent properties [ 23 , 24 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…So far, hydrazone-based metal complexes have received considerable attention from chemists in many applications such as chromogenic reagents in the spectrophotometric determination of transition-metal ions, metal extracts and biologically active compounds [ 9 ]. They have also been demonstrated to possess diverse pharmacological properties [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], catalytic properties [ 18 , 19 ], adsorption properties [ 20 , 21 ], electrochemical properties [ 22 ], luminescent properties [ 23 , 24 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Some groups demonstrated that copper complexes cause elevation of DNA damage-indicating proteins. 57 In the context of cancer therapy, the quantification of γH2AX is a useful biomarker for evaluating the DNA damage caused by diverse compounds. Previously we showed by CD that both coordination complexes modified the DNA structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Overall, it is well-known the variety of alternative mechanisms of action by which metal complexes may exert their biological or pharmacological activity, besides impacting cell cycle [4,8,67]. Various nickel complexes have shown to act through the formation of ROS species and inducing mitochondrial-mediated apoptosis [56,74,81,82] or by activating the tyrosine kinase proapoptotic pathway [58]. In addition, other ruthenium complexes have also demonstrated to exert activity through the apoptotic pathway via cleaved PARP, caspase-3 and caspase-9 [64,83]; lysosome-mediated apoptosis [62]; necrosis [60]; and possibly inhibiting DNA replication by binding to DNA strands [59].…”
Section: Cell Cycle Analysismentioning
confidence: 99%